Enabling growth in the new economy: Industrial policy choices in a world of disruptive technological change - Simon Lacey (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
This paper examines recent technological developments and how they could impact efforts by policymakers and political leaders in developing countries to harness trade and investment liberalization to achieve economic development outcomes. It begins by discussing some of the proven elements to moving up the development ladder but then warns that the tried and trusted methods and pathways could be closing in light of new technological developments such as automation and artificial intelligence, the impact of which on labor markets promises to be disruptive in the short to medium term. The paper provides a set of policy prescriptions that governments could and should be contemplating in order to position their economies to benefit from the opportunities of the new economy but also to shelter their workforces from any possible downsides that these new and disruptive technologies may bring with them. Perhaps the most important finding this report has to offer is that the most decisive factor in achieving genuine change and tangible development improvements is political will and the determination to override the resistance to change that will inevitably come from entrenched interests (including political and economic elites) that benefit from the status quo. This is about improving the state of economic governance in countries and can only be achieved by embarking upon serious and results-driven reform. The report discusses some areas of reform that seem particularly important in light of the technological transformations unfolding, namely skills and education, empowering the private sector and embracing digitization. It was written before the global health pandemic and ensuing economic shocks unleashed by COVID-19, but its findings remain relevant and the urgency for implementing its recommendations has increased as a result of the many sudden and drastic changes the global economy has been forced to undergo as a result of this crisis.
Keywords: F13; L52; L88; O24; O38; 330; economic governance; private sector reform; automation; artificial intelligence; LDCs; Fourth Industrial Revolution